Climate-friendly but socially rejected energy-transition pathways: The integration of techno-economic and socio-technical approaches in the Nordic-Baltic region. (September 2020) - Bolwig, Simon; Bolkesjø, Torjus Folsland; Klitkou, Antje; Lund, Peter D.; Bergaentzlé, Claire; Borch, Kristian; Olsen, Ole Jess; Kirkerud, Jon Gustav; Chen, Yi-kuang; Gunkel, Philipp Andreas; Skytte, Klaus
Highlights: Analysis of social acceptance combined with energy-system scenario modelling. Social acceptance involves environmental, health, and distributional factors. Results illustrate important energy-system effects of low social acceptance. Low social acceptance of onshore wind and transmission favours local solutions. No restrictions on power transmission raise consumer prices in the Nordic-Baltics. Abstract: A framework to account for social acceptance in the modelling of energy-transition pathways is outlined. The geographical focus is on the Nordic-Baltic energy region and the technological focus is on onshore wind power and power transmission, which are considered key technologies in achieving carbon-neutral energy systems in northern Europe. We combine qualitative analysis of social acceptance with quantitative assessments of scenarios using techno-economic energy-system modelling. Key factors in and consequences of social acceptance are identified, especially environmental, health, and distributional factors, as well as costs for developers and society. The energy system analysis includes four scenarios illustrating the system effects and costs of low social acceptance. The results indicate that if low social acceptance were to restrict investments in onshore wind power, costlier solar photovoltaics and offshore wind power would step in. Greater social acceptance cost for onshore wind and transmission lines favours local solutions and a more balanced renewable energy mix. There are important distributional effects: no restrictions on transmission line investments benefit power producers while raising consumer prices in the Nordic-Baltic energy region, while very low social acceptance of onshore wind power would lead to 12% higher consumer costs. The results imply that socio-technical and political factors such as social acceptance may significantly affect transition pathway scenarios based on techno-economic variables alone. Therefore, the techno-economic, socio-technical and political layers of co-evolution of energy systems should be considered when analysing long-term energy transitions. It is important to link energy-system models with a consideration of the dynamics of socio-technical factors.